Language abilities and phonological information processing mediate the association of spelling with bilingualism and socioeconomic status - Schöfl, Martin; Weber, Christoph; Steinmair, Gabriele; Zepnik, Sabine; Grimm, Angela (Frontiers in Education, 2024)
Research to date has focused on the associations between spelling and (i) its precursors (phonological information processing and language) and (ii) socioeconomic status and bilingualism. Studies have also indicated that bilingualism and parental education are associated with spelling precursors. Whereas these associations have previously been analyzed individually, this study proposes a mediation model in which the effects of socioeconomic status and bilingualism on spelling are mediated by phonological information processing and language skills. For this purpose, we assessed the competencies in spelling precursors of 1012 first graders at the beginning of the first grade, and tested their spelling abilities at the end of the first grade. We then applied a structural equation modeling approach to test the mediation model. In line with the mediation hypothesis, the results show indirect effects of parental education (as a measure of socioeconomic status) on spelling via language and phonological information processing. In addition to mediation we also found a direct effect of SES on spelling performances. For bilingualism, the results support full mediation, more specifically an indirect effect via language only. Notably, we found no effect of bilingual status on phonological information processing.